Evaluation of antinutritional factors in the digestibility of proteins from Amaranthus caudatus seeds - Silva, Daniela Regiane da; Cordeiro, Helon Guimarães; Oliveira, Fhelipe de; Soares, Bruno; Tarabal, Vinicius; Granjeiro, Paulo Afonso; Silva, José Antônio da (Food Science and Technology, 2025)
With population growth, the need for natural products with a good nutritional balance increases. Digestibility is an important factor that defines the nutritional diet and the quality of proteins. This work aims to evaluate the protein digestibility of Amaranth (Amaranthus caudatus) seeds. Amaranthus seed extracts showed inhibitory activity and hemagglutinating activity. In the simulating gastric fluid condition, hydrolysis products were detected, a 70 kDa band, which does not appear in the control. After the heating treatment, pepsin easily digested the 29 kDa lectin bands and a gradual digestion of the 12 and less than 10 kDa bands, probably the protease inhibitors. In the simulating intestinal fluid evaluation, without heating, the bands of 29, 12, and less than 10 kDa showed resistance to digestion. After heat treatment, the intensity of the corresponding bands 12 and those less than 10 kDa gradually decreased compared to the band of 29 kDa, which was digested quickly. Amaranthus seeds showed antinutritional factors, inhibitors, and lectins, demonstrating that at appropriate treatment and increased temperature it can improve more the efficient activities of digestive enzymes. Therefore, this work shows the importance of cooking for better protein absorption of Amaranthus seeds, making them a good source of amino acids.